Prevalence of Molar Incisors Hypomineralisation (MIH) in primary school children - Praptiwi, Yenni Hendriani; Prayitno, Natanael Dwi; Sukmasari, Susi (Padjadjaran Journal of Dentistry, 2019)
Introduction: Molar Incisor Hypomineralisation (MIH) is an enamel defect with white, yellow or black colour due to minerals insufficient during tooth development. The abnormality of prismatic enamel structures and tooth hypersensitivity on patients with MIH may disturb the success rate of restoration. The objective of this research was to determine the prevalence of MIH in primary school children. Methods: A cross-sectional study with purposive sampling on 619 primary school children at Pasteur Urban Village of Bandung City, Indonesia. All dentition were scored using the European Association of Paediatric Dentist (EAPD) MIH scoring sheet, and oral hygiene status assessment with simplified OHI. All data were descriptively described using distribution table. Results: Distribution of MIH on total of 619 children were scored as follows: 0,1,1a, 2, 2a, 3, 4, 5, 6, 7, 8, 9,10 (0 = free enamel defect; 6, 7, and 8 = alteration to non MIH; 1 -5 and 9 -10 = MIH) with frequencies 417(67.36%), 39(6.30%), 60(.65%), 13(2.10%), 0(0.00%), 7(1.13%), 0(0.00%), 4(0.65%), 0(0.00%), 26(4.20%), 58(9.36%), 0(0.00%), and 49(7.91%) respectively. Conclusion: Prevalence of children with MIH in primary school is quite high (19% (118 out of 619 participants)). The highest prevalence is found at the 11 years old group with 49 participants (36.84%), while the prevalence in boys (83 (62.4%)) is found to be higher than girls (50 (37.59%)).Keywords: Prevalence, Molar Incisor Hypomineralisation (MIH), primary school children